Dominant and Satellite Markets: A Study of Dually-Traded Securities - Garbade, Kenneth D.; Silber, William L. (The Review of Economics and Statistics, 1979)
Magee, Stephen P., Currency Contracts, Pass-through and Devaluation, Brookings Papers on Economic Activity (1, 1973), 303-323. , Prices, Incomes and Foreign Trade, in Peter B. Kenen (ed.), International Trade and Finance: Frontiers for Research (New York: Cambridge University Press, 1975). Malinvaud, Edmond, Statistical Methods of Econometrics (Amsterdam: North-Holland Publishing Company, 1970). Nerlove, Marc, Spectral Analysis of Seasonal Adjustment Procedures, Econometrica 32 (July 1964), 241-285. Orcutt, Guy H., Measurement of Price Elasticities in International Trade, this REVIEW 32 (May 1950), 117-132. Pearce, Ivor F., International Trade (London: Macmillan, 1970). Robinson, Joan, Foreign Exchanges, American Economic Association, Readings in the Theory of International Trade (Homewood, Illinois: Richard D. Irwin, Inc., 1949). Stern, Robert M. , The Balance of Payments (Chicago: Aldine Publishing Co., 1973). Stern, Robert M., Jonathan Francis, and Bruce Schumacher, Price Elasticities in International Trade (Toronto: Macmillan of Canada, 1976). United States Department of Commerce, The National Income and Product Accounts of the United States, 1929-1965, Statistical Tables, a supplement to the Survey of Current Business (Washington, D. C.: U. S. Government Printing Office, 1966). Survey of Current Business (July editions) (Washington, D. C.: U. S. Government Printing Office, 19681974). Whitman, Marina v. N., Global Monetarism and the Monetary Approach to the Balance of Payments, Brookings Papers on Economic Activity (3, 1975).